Conventional Sharia And Financial Statements - Dian Permata Sari; Nurul Shofia Mardhiah; Nasri Arifin (Proceeding International Seminar of Islamic Studies, 2019)
In every company or financial institution, both conventional or Sharia-based institutions must have financial reports. The financial statements are a picture of the situation about the assets, liabilities, equity, income and expenses that occur in a company or financial institution itself. The financial statements are prepared Periodically, the things that are reported will then be Analyzed so that it can know the conditions and the current position of the company. The financial statements presented by the company will be very important for management and company owners. In addition, the financial statements of a company or financial institution Also will be very useful for the government, creditors, investors, and suppliers. Then, is there a difference between conventional and Islamic financial financial statements statements.